Analysis of the Use of Shopee Paylater in E-Commerce on Consumer Finance: An Islamic Economic Perspective - Imam Kamaluddin; Amin Fonda Astiti Rob Rahayu (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to determine the impact of PayLater on consumer finance and Islamic economic views on PayLater. Technology and information are developing very quickly, and this aims to make it easier for humans to meet increasingly complex needs. One of them is PayLater, which is used for online transaction payments. However, some things are considered inappropriate behind the convenience offered and can plunge users into debt traps. This study uses a type of qualitative research with a library research approach and is analyzed using content analysis. The result of this study is that PayLater must be balanced with good financial literacy because, in addition to offering convenience, some things can harm its users, such as triggering consumptive behavior and debt entanglement. In Islamic economics, PayLater is not allowed or prohibited because there are indications of riba in the fine of 5%, an additional fee of 2.95%, and administrative costs taken from the percentage of the transaction value of 1%.